Evaluation of the effect of learning on the full extent of inspiratory and expiratory pressure in healthy adults - Giuliani, Beatriz Branco; Olavo, Glaucia Cristiane; Machado, Kátia De Souza; Abreu, Luiz Carlos De; Valenti, Vitor Engracia; Raimundo, Rodrigo Daminello (Mavera Edições Técnicas e Científicas Ltda, 2016)
BACKGROUND: Measurements of maximal inspiratory and expiratory pressure are used to assess the pressure developed by the respiratory muscles and the passive elastic recoil of the pulmonary system. Such measurements are also used as criteria for weaning from mechanical ventilation, to determine the functional consequences of several systemic diseases and the development of lung diseases and neuromuscular disorders. The test in na outpatient setting is easy to perform, well tolerated and has predictive valueOBJECTIVE: To verify the presence of a learning effect in measurements of maximal inspiratory and expiratory pressures.METHODS: We performed 15 sequential measurements of Maximal Inspiratory Pressure and 15 of Maximal Expiratory Pressure in 71 individuals. Results for both series were compared throughout each series.RESULTS: The comparison between the first and the other measurements showed no statistically significant differences. (p > 0.05).CONCLUSIONS: There was no learning effect with 15 repeated measurements of Maximal Inspiratory or Expiratory Pressure in healthy adults.

INTRODUÇÃO: Medidas de pressão inspiratória máxima e pressão expiratória máxima são usados para avaliar a força desenvolvida pelos músculos respiratórios. Tais medidas são também utilizadas como critérios para o desmame da ventilação mecânica, para determinar as consequências funcionais de várias doenças sistêmicas e do desenvolvimento de doenças pulmonares e neuromusculares.OBJETIVO: Verificar a presença do efeito de aprendizado nas mensurações de pressão inspiratória e expiratória máximas.MÉTODO: Foram realizadas 15 medições sequenciais de pressão inspiratória máxima e 15 de pressão expiratória máxima em 71 indivíduos. Os resultados para ambas as séries foram comparados ao longo de cada sérieRESULTADOS: As comparações entre a primeira e as demais medidas não apresentaram diferenças estatisticamente significativas (p > 0,05).CONCLUSÃO: Não houve efeito aprendizado em 15 medidas repetidas de pressão inspiratória máxima ou pressão expiratória máxima em adultos saudáveis.
AVALIAÇÃO DO EFEITO DE APRENDIZADO NA MENSURAÇÃO DAS PRESSÕES INSPIRATÓRIA E EXPIRATÓRIA MÁXIMAS EM ADULTOS SAUDÁVEIS
Keywords: Inspiratory pressure; Learning effect; Respiratory muscles.; pressão inspiratória máxima; efeito aprendizagem; músculos respiratórios